Tantangan dan Prospek : Implementasi Prinsip-Prinsip Demokrasi dalam Hukum Tata Negara Indonesia - Rohmatillah, Arman Rohmatillah; Moh. Sa’diyin; Ahmad Afan Zaini (JOSH: Journal of Sharia, 2023)
This journal discusses the implementation of democratic principles in the context of Indonesian constitutional law. This study aims to analyze the challenges and prospects in implementing democratic principles in the Indonesian state administration system. The research methods used include literature studies, analysis of laws and regulations, and field research. Based on the research results, it was found that the implementation of democratic principles in Indonesia is faced with various challenges, including conflicts of political interests, corruption, weak public participation, and fulfillment of human rights. However, there are also positive prospects for the implementation of democratic principles, such as legal reform efforts, increasing public awareness, and the active involvement of civil society organizations. This research provides policy recommendations to improve the implementation of democratic principles in Indonesian constitutional law, including strengthening transparency, accountability, public participation, and protection of human rights. Keywords: implementation, democratic principles, constitutional law, challenges, prospects, Indonesia.